One arachnid taxonomist, 1,000+ species described and the implications for conservation - Sullivan, Gregory T.; Ozman-Sullivan, Sebahat K. (Zootaxa, 2026)
The megadiverse invertebrates are a fundamental component of global ecological functioning. There are estimated to be millions of unnamed species of terrestrial and aquatic arthropods alone. Limited expertise and funding mean that taxonomists across the world are only able to name a minute proportion of the undescribed species every year. One of the outstanding contributors is Dr. Mark Stephen Harvey, an Australian arachnid specialist, whose ‘obsession’ with that group began nearly 50 years ago. In 2025, he alone and with colleagues published 137 new species and 17 new genera. In the same year, Dr. Harvey joined the exclusive group of taxonomists who have described 1,000 species; most of his extraordinary total are pseudoscorpions and spiders, but also includes millipedes, scorpions, water mites and velvet worms. The efforts of Dr. Harvey and other taxonomists in cataloguing global biodiversity are vital to the study of disciplines such as ecology, evolution, biogeography, genetics and speciation; public education; and the promotion and implementation of biodiversity conservation across the planet.